PELATIHAN INOVASI KUDAPAN DARI JAMUR TIRAM DI DESA CIHERANG KECAMATAN GUNUNG SARI KABUPATEN SERANG - Listiawati Listiawati; Zenny Purwaningsih; Adelia Adelia; Binti Masruroh; Faiddatul Fuadah (Batara Wisnu : Indonesian Journal of Community Services, 2021)
Oyster Mushrooms can provide advantages and disadvantages. From some mushrooms that can be processed to become snacks that can be consumed. Mushrooms are also sometimes used as ingredients for traditional medicine. One of the mushrooms that can be processed into food is oyster mushroom, which has been getting a lot of attention lately. Mushrooms that have a distinctive white color are known as Shimeji (Japan), Abalone Mushroom or Ayster Mushroom (Europe or America) and Supa Liat (West Java). Jamut Oyster has a high nutritional content so it can be consumed for those who are on a diet. Usually mushroom farmers sell oyster mushrooms in a fresh state. Currently in Banten there are not many who sell oyster mushrooms as processed food, although financially selling after processing is much more profitable than selling fresh mushrooms. From the results of surveys and interviews with the community around Ciherang Village, Gunung Sari sub-district, it turns out that they have not received information about how to process mushrooms to make various types of snacks. The people's knowledge is limited, which is usually only vegetables or stir-fried. In our community service, we discuss how to process oyster mushrooms. The purpose of this training is to provide partners with knowledge of processing oyster mushrooms into nuggets, shredded and broth. Partners are given information on how to make processed oyster mushrooms with good quality. Then given knowledge about how to market through online media with attractive packaging